2020
DOI: 10.2967/jnumed.120.244145
|View full text |Cite
|
Sign up to set email alerts
|

Interim PET Evaluation in Diffuse Large B-Cell Lymphoma Using Published Recommendations: Comparison of the Deauville 5-Point Scale and the ΔSUVmax Method

Abstract: The value of interim 18F-fluorodeoxyglucose positron emission tomography (iPET) guided treatment decisions in patients with diffuse large B-cell lymphoma (DLBCL) has been the subject of much debate. This investigation focuses on a comparison of the Deauville score and the deltaSUVmax (ΔSUV max) approachtwo methods to assess early metabolic response to standard chemotherapy in DLBCL. Methods: Of 609 DLBCL patients participating in the Positron Emission Tomography-guided Therapy of Aggressive non-Hodgkin Lymphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…The results obtained with both quantitative methods imply that the currently recommended threshold to identify high-risk patients by virtue of the visual Deauville scale (score 1-3 versus 4-5) is of limited value. This conclusion complements our previous finding that SUVmax is superior to Deauville for interim PET-based outcome prediction when recommended thresholds are employed (17). A cut-off between scores 4 and 5 of the visual scale may be more appropriate, in particular when interim PET is used to select patients for more aggressive therapies.…”
Section: Discussionsupporting
confidence: 83%
“…The results obtained with both quantitative methods imply that the currently recommended threshold to identify high-risk patients by virtue of the visual Deauville scale (score 1-3 versus 4-5) is of limited value. This conclusion complements our previous finding that SUVmax is superior to Deauville for interim PET-based outcome prediction when recommended thresholds are employed (17). A cut-off between scores 4 and 5 of the visual scale may be more appropriate, in particular when interim PET is used to select patients for more aggressive therapies.…”
Section: Discussionsupporting
confidence: 83%
“…However, MTV cut-offs were different, and it is unclear whether and/or to which extent this relates to the use of different semi-automated delineation algorithms; Oñate-Ocaña used a 40%SUVmax threshold, Zhang a 41%, Wu a 42% and Malek a 37%SUVmax threshold and a gradient-based segmentation method (Gradient), while Islam applied a SUV4.0 threshold and Yang and Mikhaeel a SUV2.5 threshold (7)(8)(9)(15)(16)(17)34). This precludes any meaningful meta-analysis to build the case of evidence for MTV as a predictor for clinical outcome additional to (delta)SUVmax and the five-point DS (10,11). The latter particularly for I-PET DLBCL studies, since correlation between MTVs obtained by different segmentation methods is generally low for lesions with SUVmax<10 (Supplemental Figure 3) frequently prevailing at I-PET in contrary to baseline PET.…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination between true non-responders and responders might improve by quantification (e.g. the relative change of standardized tracer uptake) (5)(6)(7)(8)(9)(10)(11). Quantification will reduce observer variability, and this is essential for successful clinical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…This high recurrence with negative iPET indeed questions the diagnostic accuracy of Deauville scores 1-3 (no uptake or ≤ mediastinal or ≤ liver uptake) to interpret an iPET as CMR. Recently published results from Positron Emission Tomography-guided Therapy of Aggressive non-Hodgkin Lymphomas (PETAL Trial) found better diagnostic accuracy of delta SUVmax (∆SUVmax ≤66%) than Deauville scoring >3 on iPET for dose intensification to avoid over-treatment (Rekowski et al, 2020). However, DS ≤3 and ∆SUVmax ≤66% were found to have comparable event free survival (EFS) in PETAL trial (Rekowski et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recently published results from Positron Emission Tomography-guided Therapy of Aggressive non-Hodgkin Lymphomas (PETAL Trial) found better diagnostic accuracy of delta SUVmax (∆SUVmax ≤66%) than Deauville scoring >3 on iPET for dose intensification to avoid over-treatment (Rekowski et al, 2020). However, DS ≤3 and ∆SUVmax ≤66% were found to have comparable event free survival (EFS) in PETAL trial (Rekowski et al, 2020). Kwonet al, (2016) used DS-1 for negative iPET in homogenous population but the relapse rate is similar to our study with DS ≤ 3 as negative iPET in homogenous population with standardized imaging and reporting protocols.…”
Section: Discussionmentioning
confidence: 99%